The Role of Targeted Therapy in the Management of High-Risk Resected Kidney Cancer: What Have We Learned and How Will It Inform Future Adjuvant Trials. Issue 5 (September 2020) - Brown, Landon C.; Zhang, Tian; George, Daniel J.
Abstract : Abstract: The primary treatment for localized renal cell carcinoma (RCC) is surgical resection with curative intent. Despite this, many patients, especially those with high-risk features, will develop recurrent or metastatic disease. Antiangiogenic therapies targeting vascular endothelial growth factor have been a mainstay of treatment of advanced RCC for more than 10 years. Evidence supporting the use of these therapies in the adjuvant setting is mixed, although one clinical trial, S-TRAC, has shown improvements in disease-free survival with 1 year of adjuvant sunitinib among patients with clear cell histology and high-risk features, leading to the first US Food and Drug Administration approval of an adjuvant therapy for high-risk RCC patients. Further investigation into combination therapies with immunotherapy, neoadjuvant approaches, and patient selection will be key to determining optimal adjuvant therapy regimens to improve outcomes and increase cure rates for patients with localized RCC.